The Frustration in Scientific Practice - Sloup, Ondřej (Teorie vědy / Theory of Science, 2015)
This study deals with two related phenomena that take place in scientific environment. The first one under review is the frustration in scientific practice which is closely associated with the desire for recognition of our own research by the scientific community. Both of these phenomena are strongly tied to the problematic aspect of recognition given by the academic community. The aforementioned occurrences are yet closely linked with the central theme of philosophy and sociology of science: who decides what will be subjected to the scientific inquiry? The article deals with Merton's myth of immediate recognition in scientific discovery and for its deep analysis uses the excursion into economic field. Text further points out on malfunction of the described Mertonian myth in contemporary science by the use of examples from scientific practice (mainly from the lives of Karl Popper and Michael Faraday). Final argument proposes solutions to described problems together with their deconstruction. The text also represents a critical review of two studies by Joseph Agassi, a stubborn supporter of critical rationalism. Because it was Agassi, a loyal disciple of Karl Popper, who discussed in detail the implications of scientific exclusion and unwillingness to listen.